Potential repellency of cedarwood oil from a novel extraction method to stored product insects - Albin, Chloe E.; Quellhorst, Hannah; Campbell, James; Eller, Fred; Morrison III, William R. (My University, 2018)
Producers lose 10-30% of crops during storage, processing, and marketing after harvest each year to stored product insects (1,2). Globally, there has been a rise in insecticide resistance to phosphine, the most common fumigant for these pests (3). As a result, producers need to diversify post-harvest IPM methods to preserve existing tools. One alternative strategy is push-pull, whereby a repellent is used to “push” an insect away from the commodity of interest, while also simultaneously “pulling” the insects to an alternate location away from the commodity using an attractant (4)(Fig. 1). This system notably requires a long-distance repellent. One potential repellent includes cedarwood oil, which has shown repellency to termites and ants (5,6). A novel extraction process for this compound has been developed, which leaves many of its main constituents intact (7). However, to date, this compound has never been assessed for repellency to post-harvest insects.
Keywords: Fall 2018